(untitled) (Conference on English Language Teaching, 2023)
n principle, E-learning is learning that use electronic service as a tool. Quizizz is one of these E-learning web applications. Quizizz is a competititve games. This application has been widely used by teachers around the world in learning activities, such as making online quizzes which are currently rife. This study use a quantitative descriptive method through a survei approach that focuses on effectiveness in using Quizizz in teaching english. This research was conducted at the Junior High School Beringin in Deli Serdang district. The subject of this study were 9th grade of Junior High School students in Beringin, totaling 26 students who were studying English with using Quizizz application. The researcher collected data by using a questionnaire, in collecting data the researcher used several method, namely (1) the researcher gave 10 statement related to Quizizz in teaching English, these statements were sent via google drive, (2) then students choose the answer SS, S, TS, STS on the questionaire. To analyze the data the researcher determined the percentage of each questionnaire answered by the students. So the results of this research that average percentage of effectiveness was strongly agree (SS) 53,6%, agree (S) 60,7%, disagree (TS) 39,3%, strongly disagree (STS) 10,7%.